Value stream mapping: an application lean in the process of accountability in a philanthropic hospital - Moraes, Cristine Frare; Bonato, Samuel Vinícius; Junges, Vanessa de Campos; Moura, Gilnei Luiz de; Wachs, Priscila (Revista de Administração da UFSM, 2023)
Objective: This study aimed to map the value flow of medical records of a philanthropic hospital, identifying opportunities for improvements in the process. Design/methodology/approach: A qualitative research of descriptive and exploratory bias was developed, in which the sources of evidence emerged from participant observation and documentary analysis. Therefore, data collection took place for three months in 2021, which took place in the administrative sectors of a large philanthropic hospital, and the process chosen to be mapped and analyzed was the surgical record. Result: The analysis of the process took place from the patient’s discharge to the delivery of the accounts to the typing/billing sector, where the routine of the post desks was observed and the current flows were mapped through the Value Stream Mapping tool (VSM), with several wastes being detected. The time spent in the process was approximately 56 days, after the suggested improvements and drawing up the map of the future situation, this time was reduced to 28 days. With the application of the tool, waste was identified and eliminated in the mapped process, generating a possibility of cost reduction. Originality/value: The study stands out as it seeks to link the context of value stream mapping in a hospital space, opening space for new research and contributing to practical results.